Réponses

Meilleure réponse !
2014-03-19T09:55:42+01:00
2(x+1)+3 (x-1)=0    
2x+2+3x-3=0
5x-1=0
X=1/5
           3(2x+1)-4 (x-2)=2(x/2+1)  

6x+3-4x+8=2(x+2/2)
2x+11=2X+4/2
2X+11=X+2
2X+11-X-2=0
X+9=0
X=-9


et tu fais de mémé pour les autres , tu développes et tu recouds ton équation 
 
               (2x+1)(x-2)(x+1)=0  
   

2 (x+1)-3 (x-2)=-(2x+1)    

   
            x-1/2=3x+1/4
2014-03-19T10:02:19+01:00
2(x+1)+3 (x-1)=0    
2x+2+3x-3=0
 5x-1=0
 5x=1
 x=1/5                 

3(2x+1)-4 (x-2)=2(x/2+1)
6x+3-4x+8=x+2
 2x+11=x+2
 2x-x=2-11
 x=-9              

2x+1)(x-2)(x+1)=0
 2x+1=0     ou    x-2=0    ou       x+1=0
 2x=-1                x=2                  x=-1
 x=-1/2  

2 (x+1)-3 (x-2)=-(2x+1)
2x+2-3x+6=-2x-2
 -x+8=-2x-2
 2x-x=-8-2
 x=-10               

 x-1/2=3x+1/4
3x-x=-1/2-1/4
2x=-2/4-1/4
2x=-3/4
x=-3/(4*2)
x=-3/8